Intimidasi Pembela HAM: Kasus Penyerangan Andrie Yunus (Maret - Mei 2026) - Sahputra, Aditya; Asiyah Rambe , Alda; Malau , Christover Willy; Tahajudin, Raihan Ahmad; Steven Sihotang, Grasius (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The attack on Andrie Yunus in March 2026 became one of the significant incidents highlighting the condition of human rights defender protection in Indonesia. As an activist actively involved in advocacy activities and public policy oversight, Andrie Yunus was subjected to violence allegedly related to his human rights advocacy work. This study aims to analyze the forms of intimidation against human rights defenders through a case study of the attack on Andrie Yunus during the period of March–May 2026. The research employed a qualitative approach using a case study method and library research techniques. Data were collected from academic journals, human rights organization reports, official documents, and other relevant publications. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the Andrie Yunus case reflects the continuing threats faced by human rights defenders in carrying out their advocacy activities. The intimidation not only affected the victim personally but also had the potential to create fear among civil society groups and narrow the space for civil liberties in democratic life. Furthermore, the case highlights the crucial role of the state in ensuring protection, security, and legal certainty for human rights defenders. Therefore, strengthening protection mechanisms and improving law enforcement are necessary to prevent similar incidents from occurring in the future.